A Comprehensive Review of Architectural, Algorithmic, and Technological Innovations for Energy-Efficient 6G Communication Networks - Kapileswar, Nellore; Simon, Judy (Journal of Trends in Computer Science and Smart Technology, 2025)
Due to the evolution of 6th generation (6G) communication networks, it has been witnessing an increasing need for ultra-high data rates, massive connection, low latency, and intelligence. However, some tasks need to be performed for fulfilling this demand through preserving the energy consumption. In this article, it is providing an extensive assessment of technological, computational, and architectural developments for optimizing energy efficiency during developing 6G communication networks. In context of architectural advancement, it is assessing intelligent reflecting surfaces, Green cell-free massive MIMO, and hierarchical edge-cloud computing architectures. They help decrease energy consumption during processing, device, and transmission, according to those architectures. The capabilities of AI-driven network management, energy-conscious resource allocation, and reinforcement learning optimization for optimizing energy efficiency in an effective manner through computing capabilities of AI have been described. The role of technological innovations like energy harvesting, integrated sensing and communication, ultra-low-power transceivers, and terahertz transmission in lowering operational network costs has been discussed too. In this review article, it is discussing THz wave communication and Green cell-free massive MIMO technology particularly.
Keywords: 6G Generation Networks; Energy Efficient; Network Management; Artificial Intelligence (AI); CF-mMIMO; THz Waves